Case Report: Missing zinc finger domains: hemophagocytic lymphohistiocytosis in a GATA2 deficiency patient triggered by non-tuberculous mycobacteriosis - Xin Huang; Bingxuan Wu; Di Wu; Xiaoming Huang; Min Shen (Frontiers in Immunology, 2023)
Haploinsufficiency of GATA2, also known as GATA2 deficiency, leads to a wide spectrum of clinical manifestations. Here we described another 28-year-old man with a GATA2 variant who also suffered from hemophagocytic lymphohistiocytosis(HLH), who was finally diagnosed with HLH triggered by Mycobacterium avium bloodstream infection due to primary immunodeficiency. We reviewed GATA2 deficiency patients with HLH and found that GATA2 variants causing loss of zinc finger domains were associated with HLH, and erythema nodosa might be an accompanying symptom.